Answer:
y = -¾x + 3
Explanation:
Given the equation in standard form, 3x + 4y - 12 = 0, we must isolate the y in order to make it the subject of the equation.
The first step is to add 12 to both sides of the equation:
3x + 4y - 12 + 12 = 0 + 12
3x + 4y = 12
Next, subtract 3x from both sides:
3x - 3x + 4y = - 3x + 12
4y = -3x + 12
Lastly, divide both sides by 4 to isolate y:
![(4y)/(4) = (-3x + 12)/(4)](https://img.qammunity.org/2022/formulas/mathematics/college/78gw4hrg74b0txa3uxybz9xu7xtnx1jh9w.png)
y = -¾x + 3